If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3v + 15 = 6(v + 4) Reorder the terms: 15 + -3v = 6(v + 4) Reorder the terms: 15 + -3v = 6(4 + v) 15 + -3v = (4 * 6 + v * 6) 15 + -3v = (24 + 6v) Solving 15 + -3v = 24 + 6v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-6v' to each side of the equation. 15 + -3v + -6v = 24 + 6v + -6v Combine like terms: -3v + -6v = -9v 15 + -9v = 24 + 6v + -6v Combine like terms: 6v + -6v = 0 15 + -9v = 24 + 0 15 + -9v = 24 Add '-15' to each side of the equation. 15 + -15 + -9v = 24 + -15 Combine like terms: 15 + -15 = 0 0 + -9v = 24 + -15 -9v = 24 + -15 Combine like terms: 24 + -15 = 9 -9v = 9 Divide each side by '-9'. v = -1 Simplifying v = -1
| 5x+7=9x-24 | | 8X-4p-5x= | | 8x-12=5x+25 | | 8.1(4.6)= | | 2x+19=9x+6 | | 2x-3+6x-8=5x+4 | | 4/5=9/10 | | 5v-4.2=8.3 | | p-(17)=-23 | | -11x=-6 | | 2x^2=0.08 | | -5/8=3/4=5/8 | | 59=-x/8 | | 4x=a-6 | | 15(x)+85(y)=2556 | | 3(1+-1y)=8+(-5y) | | x^3-6x^2-15x+40=0 | | -5=-27w | | -w/9=-50 | | -2w+5(w-2)=-19 | | -39=3(v+3)+5v | | 9x+4y=10 | | 1/4x1/4x1/4x1/4 | | 3m-12=3(8m+3) | | 8m^2+72m-16=0 | | 5(2z-1)-5(z+9)=2(z+1) | | 3(4a+5)=3+6a | | 6-6n=6(6n+1) | | 2x^2-25x-54=0 | | -7+5x=-7(1+8x) | | 7x-8y=-18 | | ^4√(((3x^8)(y^2))/(8x^2)) |